Ogień życia. Wiersz Adama Zagajewskiego O mojej matce - Czabanowska-Wróbel, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
Any interpretation of one of the most personal poems written by Adam Zagajewski provides a good opportunity to reassess in the new light the elegiac, deeply personal body of his poetry, as well as the role of recollections and memory in the poet’s poetical and essayist writing. The work is interpreted not only within the parental context of the literary output of the author of the essay Lekka przesada [A slight exaggeration] (2011), but also against the background of the important theme in Polish poetry, including modern poetry, i.e. the motif of the mother. The title for the present sketch has been drawn from the essay The Fire of Life, the apology of poetry authored by Richard Rorty, and stresses its unique role in expressing human experience, indicated by the American philosopher.